CHANGE MANAGEMENT AS MARKETING POLICY TO ATTRACT ADEQUATE WORKFORCE. CASE STUDIES FROM INTERNATIONAL AND GREEK EXPERIENCE - ΑspridisG.; Sdrolias, L.; Vasiliadis, L.; ΚyriakouD.; GrigoriouΙ. (European Scientific Journal, ESJ, 2014)
Managing change is a structured effort whereby individuals and groups of companies attempting to leave a certain situation going to another much better. It is essentially an organisational process aimed at helping employees to accept the organisational changes. Especially in times of crisis, organisational change can help to combat this, the expansion of the business and especially abroad, but also to serve as a marketing policy to attract and select the most capable executives. This can be done because of the fact that organisational change is addressed essentially to people whom wants are to develop and make them better suited to the new conditions. Besides, it is assumed that an organisational change to be achieved requires leaders with special skills in communication, in prediction of future states and in executives that can address the human side of workers. In this paper it will be therefore tried to determine whether change management can act as a mechanism for attracting suitable staff. Could it be the central marketing policy for staffing the firm? Is it able to pass on the organisational culture to new employees? For this reason a series of examples will be considered from both the Greek and the international experience to prove whether that is correct. Concerning of the completion of this work, initially will be studied the theory of change management, as well as international and Greek experience in order to form the basis for future research on the particular character of the process for attracting workers to the development of modern HRM.